Rampes: counselor characteristics in Sanghyang Siksakandang Karesian manuscript - Ade Hidayat; Sunaryo Kartadinata; Mamat Supriatna; Peni Ramanda (Universitas Negeri Padang, 2019)
The aim of this study is a description of counselor characters obtained from the values of Sanghyang Siksakandang Karesian (SSK) manuscript. Qualitative approach was used in which the data, analysis, and interpretation conformed to the principles of hermeneutics. As a method, hermeneutics was employed to interpret the text meaning within the SSK. The research procedure comprised: 1) selection of texts source, 2) dialogic process involving negotiation and re-negotiation of texts interpretation until the full understanding of the texts was gained, and 3) concept writing. The results suggest that in the SSK, there are three focal aspects supporting the counselor’s personal quality; that are: 1) religious, submissive and obidient to The Most Supernatural Power of God (Batara Seda Niskala); 2) being wastu siwong, a human being having good attitudes, excel at science, and knowledgable about the value of life; and 3) comprehensive about pangimbuh ning twah, the complementary thing toward the success of life in society. These three aspects in this study form a Rampes counselor.